Zn2+-dependent autocatalytic activity of the Bordetella pertussis CyaA-hemolysin - Raksanoh V. (2017)
© 2017 Elsevier Inc. Proteolytic degradation of the ∼100-kDa isolated RTX (Repeat-in-ToXin) subdomain (CyaA-RTX) of the Bordetella pertussis CyaA-hemolysin (CyaA-Hly) was evidently detected upon solely-prolonged incubation. Here, a truncated CyaA-Hly fragment (CyaA-HP/BI) containing hydrophobic and acylation regions connected with the first RTX block (BI 1015–1088 ) was constructed as a putative precursor for investigating its potential autocatalysis. The 70-kDa His-tagged CyaA-HP/BI fragment which was over-expressed in Escherichia coli as insoluble aggregate was entirely solubilized with 4 M urea. After re-naturation in a Ni 2+ -NTA affinity column, the purified-refolded CyaA-HP/BI fragment in HEPES buffer (pH 7.4) supplemented with 2 mM CaCl 2 was completely degraded upon incubation at 37 °C for 3 h. Addition of 1,10-phenanthroline‒an inhibitor of Zn 2+ -dependent metalloproteases markedly reduced the extent of degradation for CyaA-HP/BI and CyaA-RTX, but the degradative effect was clearly enhanced by addition of 100 mM ZnCl 2 . Structural analysis of a plausible CyaA-HP/BI model revealed a potential Zn 2+ -binding His-Asp cluster located between the acylation region and RTX-BI 1015–1088 . Moreover, Arg 997 ‒one of the identified cleavage sites of the CyaA-RTX fragment was located in close proximity to the Zn 2+ -binding catalytic site. Overall results demonstrated for the first time that the observed proteolysis of CyaA-HP/BI and CyaA-RTX fragments is conceivably due to their Zn 2+ -dependent autocatalytic activity.